Designing Online Healthcare Using DDD in Microservices Architecture. Issue 1 (June 2021) - Rizki, M; Fajar, A N; Retnowardhani, A
Abstract: Today, the system development had been transformed to service-oriented architecture. It more specific in microservices architecture to responds the agility and flexibility in software maintenance. This transformation is an important part that promoting independence, speed and security, while still kept balanced with the company's condition through comprehensive and effective steps. Culture of the development cycle of a company highly affected by the adaptation of microservices architecture. Thus, in order to achieve flexibility, speed and security, which are the main goal of adapting microservices, changes must be deliver well and sustainably. This study focused on designing of microservices architecture for health system using domain driven design (DDD) approach.